2013
DOI: 10.1161/circresaha.113.301690
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Mesenchymal Cells Rejuvenated by the Overexpression of Telomerase and Myocardin Promotes Revascularization and Tissue Repair in a Murine Model of Hindlimb Ischemia

Abstract: Rationale: The number and function of stem cells decline with aging, reducing the ability of stem cells to contribute to endogenous repair processes. The repair capacity of stem cells in older individuals may be improved by genetically reprogramming the stem cells to exhibit delayed senescence and enhanced regenerative properties. Objective: We examined whether the overexpression of myocardin (MYOCD) and telomera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 43 publications
7
72
0
Order By: Relevance
“…To date the molecular mechanisms of insulin resistance in diabetes have been explored extensively. Elevation of GLUT4 protein on cell membrane of peripheral insulin target tissues are responsible for improvement in senThis was consistent with the findings that ASC could transdifferentiate toward endothelial cells in vitro and release angiogenic factors such as VEGF, HGF, and vWF in vivo [33,34]. We thus concluded that ASC could restore islet function by reducing the apoptosis of islet cells and promoting islet vascularization.…”
Section: Discussionsupporting
confidence: 89%
“…To date the molecular mechanisms of insulin resistance in diabetes have been explored extensively. Elevation of GLUT4 protein on cell membrane of peripheral insulin target tissues are responsible for improvement in senThis was consistent with the findings that ASC could transdifferentiate toward endothelial cells in vitro and release angiogenic factors such as VEGF, HGF, and vWF in vivo [33,34]. We thus concluded that ASC could restore islet function by reducing the apoptosis of islet cells and promoting islet vascularization.…”
Section: Discussionsupporting
confidence: 89%
“…7 Analogous to previous reports, 9,10,12,49-51 we observed that the transplanted ASCs were incorporated in the vessels (RFP + /PCNA + / CD31 + ) in ischemic hindlimbs of mice, implying that some ASCs can differentiate into ECs in vivo. Moreover, the transplanted ASCs may also differentiate into vascular smooth muscle cells 52,53 and even pericyte-like cells in vivo 14 to stabilize the neovasculature and exert proangiogenic paracrine effects as well. [54][55][56] Indeed, both TP-KO ASC (RFP + /PCNA + / CD31 + ) and recipient-cell-derived (RFP -/PCNA + /CD31 + ) neovascularization were more than doubled than that in hindlimbs transplanted with WT ASCs, indicating enhanced differentiation toward ECs and paracine activity in TP-KO ASCs.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue-mesenchymal stem cells (AT-MSCs) that coexpress telomerase reverse transcriptase and MYOCD show increased levels of endogenous octamer-binding transcription factor 4, myocyte-specific enhancer factor 2c, and homeobox protein NKX2-5, and exhibit high cardiovascular regenerative potential. 109,110 These cells also show decreased frequencies of both spontaneous cell death and Fas-induced apoptosis. 109 The delivery of the telomerase reverse transcriptase and MYOCD genes into AT-MSCs was shown to restore MSCs from aged mice by increasing cell survival, proliferation, and smooth muscle myogenic differentiation in vitro.…”
Section: Rejuvenation Of Cardiac Stem Cellsmentioning
confidence: 97%